Strategi Komunikasi Humas Dinas Komunikasi Dan Informatika Dalam Mensosialisasikan Program Pelayanan Administrasi Terpadu Kecamatan (Paten) Pemerintah Kabupaten Karawang - Shabrina, Ghina; Kusumaningrum, Rastri; Panji Teguh Santoso, Made (Jurnal Ilmiah Wahana Pendidikan, 2024)
This study in-depth analyzes the communication strategies used by the Public Relations Office of Communication and Informatics in an effort to socialize the District Integrated Administrative Service Program (PATEN) run by the Karawang Regency Government in 2023. The purpose of this research is to reveal the effectiveness of various communication tactics applied in convey information and objectives of the PATEN program to various levels of society. Research data was collected through analysis of documents related to the PATEN program, in-depth interviews with relevant parties, and also through surveys involving respondents from various backgrounds. The approach used in data analysis is a qualitative approach. From the research conducted, it was found that the communication strategy used by Diskominfo Public Relations involving the use of social media, the use of online media web pages, the use of radio media, and close collaboration with local media, has succeeded significantly in increasing public understanding and participation in the PATEN Program. This research makes an important contribution to the understanding of how well-planned communication approaches can influence the effectiveness of socialization of government programs at a local scale.